Twenty-First Century Ecosystems: Managing the Living World Two Centuries After Darwin: Report of a Symposium - National Research Council (The National Academies Press, 2011)
The two hundredth anniversary of the birth of Charles Darwin, February 12, 2009, occurred at a critical time for the United States and the world. In honor of Darwin's birthday, the National Research Council appointed a committee under the auspices of the U.S. National Committee (USNC) for DIVERSITAS to plan a Symposium on Twenty-first Century Ecosystems. The purpose of the symposium was to capture some of the current excitement and recent progress in scientific understanding of ecosystems, from the microbial to the global level, while also highlighting how improved understanding can be applied to important policy issues that have broad biodiversity and ecosystem effects. The aim was to help inform new policy approaches that could satisfy human needs while also maintaining the integrity of the goods and services provided by biodiversity and ecosystems over both the short and the long terms. This report summarizes the views expressed by symposium participants; however, it does not provide a session-by-session summary of the presentations at the symposium. Instead, the symposium steering committee identified eight key themes that emerged from the lectures, which were addressed in different contexts by different speakers. The focus here is on general principles rather than specifics. These eight themes provide a sharp focus on a few concepts that enable scientists, environmental NGOs, and policy makers to engage more effectively around issues of central importance for biodiversity and ecosystem management.
Keywords: Biology and Life Sciences; Environment and Environmental Studies

In the Light of Evolution: Volume II: Biodiversity and Extinction - National Academy of Sciences (The National Academies Press, 2008)
The current extinction crisis is of human making, and any favorable resolution of that biodiversity crisis--among the most dire in the 4-billion-year history of Earth--will have to be initiated by mankind. Little time remains for the public, corporations, and governments to awaken to the magnitude of what is at stake. This book aims to assist that critical educational mission, synthesizing recent scientific information and ideas about threats to biodiversity in the past, present, and projected future. This is the second volume from the In the Light of Evolution series, based on a series of Arthur M. Sackler colloquia, and designed to promote the evolutionary sciences. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. Individually and collectively, the ILE series aims to interpret phenomena in various areas of biology through the lens of evolution, address some of the most intellectually engaging as well as pragmatically important societal issues of our times, and foster a greater appreciation of evolutionary biology as a consolidating foundation for the life sciences.
Keywords: Biology and Life Sciences

In the Light of Evolution: Volume III: Two Centuries of Darwin - National Academy of Sciences (The National Academies Press, 2009)
Two Centuries of Darwin is the outgrowth of an Arthur M. Sackler Colloquium, sponsored by the National Academy of Sciences on January 16-17, 2009. In the chapters of this book, leading evolutionary biologists and science historians reflect on and commemorate the Darwinian Revolution. They canvass modern research approaches and current scientific thought on each of the three main categories of selection (natural, artificial, and sexual) that Darwin addressed during his career. Although Darwin's legacy is associated primarily with the illumination of natural selection in The Origin, he also contemplated and wrote extensively about what we now term artificial selection and sexual selection. In a concluding section of this book, several science historians comment on Darwin's seminal contributions.
Keywords: Biology and Life Sciences; Explore Science

Thinking Evolutionarily: Evolution Education Across the Life Sciences: Summary of a Convocation - National Research Council (The National Academies Press, 2012)
Evolution is the central unifying theme of biology. Yet today, more than a century and a half after Charles Darwin proposed the idea of evolution through natural selection, the topic is often relegated to a handful of chapters in textbooks and a few class sessions in introductory biology courses, if covered at all. In recent years, a movement has been gaining momentum that is aimed at radically changing this situation.
Keywords: Education; Biology and Life Sciences

In the Light of Evolution: Volume VI: Brain and Behavior - National Academy of Sciences (The National Academies Press, 2013)
The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia--in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences--and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium "Brain and Behavior," which was sponsored by the National Academy of Sciences on January 20-21, 2012, at the Academy's Arnold and Mabel Beckman Center in Irvine, CA. It is the sixth in a series of Colloquia under the general title "In the Light of Evolution." Specifically, In Light of Evolution: Brain and Behavior focuses on the field of evolutionary neuroscience that now includes a vast array of different approaches, data types, and species. This volume is also available for purchase with the In the Light of Evolution six-volume set.
Keywords: Biology and Life Sciences

Teaching About Evolution and the Nature of Science - National Academy of Sciences (The National Academies Press, 1998)
Today many school students are shielded from one of the most important concepts in modern science: evolution. In engaging and conversational style, Teaching About Evolution and the Nature of Science provides a well-structured framework for understanding and teaching evolution. Written for teachers, parents, and community officials as well as scientists and educators, this book describes how evolution reveals both the great diversity and similarity among the Earth's organisms; it explores how scientists approach the question of evolution; and it illustrates the nature of science as a way of knowing about the natural world. In addition, the book provides answers to frequently asked questions to help readers understand many of the issues and misconceptions about evolution. The book includes sample activities for teaching about evolution and the nature of science. For example, the book includes activities that investigate fossil footprints and population growth that teachers of science can use to introduce principles of evolution. Background information, materials, and step-by-step presentations are provided for each activity. In addition, this volume:
Keywords: Education; Biology and Life Sciences

In the Light of Evolution: Volume IV: The Human Condition - National Academy of Sciences (The National Academies Press, 2010)
The Human Condition is a collection of papers by leading evolutionary biologists and philosophers of science that reflect on the Darwinian Revolution as it relates to the human condition at levels ranging from the molecular to the theological. The book focuses on understanding the evolutionary origin of humans and their biological and cultural traits. The Human Condition is organized into three parts: Human Phylogenetic History and the Paleontological Record; Structure and Function of the Human Genome; and Cultural Evolution and the Uniqueness of Being Human.
Keywords: Biology and Life Sciences

In the Light of Evolution: Volume V: Cooperation and Conflict - National Academy of Sciences (The National Academies Press, 2011)
Biodiversity--the genetic variety of life--is an exuberant product of the evolutionary past, a vast human-supportive resource (aesthetic, intellectual, and material) of the present, and a rich legacy to cherish and preserve for the future. Two urgent challenges, and opportunities, for 21st-century science are to gain deeper insights into the evolutionary processes that foster biotic diversity, and to translate that understanding into workable solutions for the regional and global crises that biodiversity currently faces. A grasp of evolutionary principles and processes is important in other societal arenas as well, such as education, medicine, sociology, and other applied fields including agriculture, pharmacology, and biotechnology. The ramifications of evolutionary thought also extend into learned realms traditionally reserved for philosophy and religion. The central goal of the In the Light of Evolution (ILE) series is to promote the evolutionary sciences through state-of-the-art colloquia--in the series of Arthur M. Sackler colloquia sponsored by the National Academy of Sciences--and their published proceedings. Each installment explores evolutionary perspectives on a particular biological topic that is scientifically intriguing but also has special relevance to contemporary societal issues or challenges. This book is the outgrowth of the Arthur M. Sackler Colloquium "Cooperation and Conflict," which was sponsored by the National Academy of Sciences on January 7-8, 2011, at the Academy's Arnold and Mabel Beckman Center in Irvine, California. It is the fifth in a series of colloquia under the general title "In the Light of Evolution." The current volume explores recent developments in the study of cooperation and conflict, ranging from the level of the gene to societies and symbioses. Humans can be vicious, but paradoxically we are also among nature's great cooperators. Even our great conflicts-wars-are extremely cooperative endeavors on each side. Some of this cooperation is best understood culturally, but we are also products of evolution, with bodies, brains, and behaviors molded by natural selection. How cooperation evolves has been one of the big questions in evolutionary biology, and how it pays or does not pay is a great intellectual puzzle. The puzzle of cooperation was the dominant theme of research in the early years of Darwin's research, whereas recent work has emphasized its importance and ubiquity. Far from being a rare trait shown by social insects and a few others, cooperation is both widespread taxonomically and essential to life. The depth of research on cooperation and conflict has increased greatly, most notably in the direction of small organisms. Although most of In the Light of Evolution V: Cooperation and Conflict is about the new topics that are being treated as part of social evolution, such as genes, microbes, and medicine, the old fundamental subjects still matter and remain the object of vigorous research. The first four chapters revisit some of these standard arenas, including social insects, cooperatively breeding birds, mutualisms, and how to model social evolution.
Keywords: Biology and Life Sciences